1997
DOI: 10.1017/s1047951100004509
|View full text |Cite
|
Sign up to set email alerts
|

Infantile scimitar syndrome with severe pulmonary hypertension: successful treatment with coil embolization of the systemic arterial supply to the sequestered lung

Abstract: Scimitar syndrome is a rare cardiopulmonary malformation. Presentation in infancy is usually associated with pulmonary hypertension and severe symptoms. We discuss treatment of such an infant. Two abnormal systemic vessels supplying the sequestered lower part of the right lung were embolized using catheter-inserted coils. The patent arterial duct was surgically ligated. These procedures resulted in a significant reduction of the shunt and the level of pulmonary hypertension, as well as in an impresssive improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…There are contradictory reports in the literature about the impact of interruption of ASAS in the early management of symptomatic infants diagnosed with SS [4, 5, 7, 9, 10]. Some studies demonstrated favorable effect to alleviate symptoms [4, 7, 8, 11, 12]. Yet others suggested an insignificant impact because ASA supplied relatively small segments of the lung to influence the shunt and PA pressure [5, 9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…There are contradictory reports in the literature about the impact of interruption of ASAS in the early management of symptomatic infants diagnosed with SS [4, 5, 7, 9, 10]. Some studies demonstrated favorable effect to alleviate symptoms [4, 7, 8, 11, 12]. Yet others suggested an insignificant impact because ASA supplied relatively small segments of the lung to influence the shunt and PA pressure [5, 9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Congestive heart failure and pulmonary arterial hypertension are particularly common in symptomatic neonates and young infants. [160][161][162]183,[189][190][191][192][193][194][195][196][197][198][199][200][201] The reasons for these features include pulmonary venous obstruction of both right or left-sided pulmonary veins, left-to-right shunting through the anomalous systemic artery or atrial septal defect, or from other coexisting cardiac lesions, or persistent pulmonary arterial hypertension of the newborn. 86,87,[160][161][162]183,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202] Rarely, the inferior caval vein may be congenitally stenotic, as in the patient reported by Tumbarello et al, 203 and others, 204 this feature also contributing to pulmonary venous obstruction (Fig.…”
Section: Scimitar Syndromementioning
confidence: 99%
“…[183][184][185][186] The observations about the causes for congestive heart failure have been confirmed by clinical and surgical reports emanating from Toronto and elsewhere. 86,87,154,162,[164][165][166]188,189,[191][192][193][194][195][196][197] The so-called scimitar sign on the frontal chest radiograph, while characteristically representing the anomalously draining right pulmonary veins, can be mimicked by other structures, including right pulmonary veins meandering through a tortuous course to the left atrium, a large anomalous systemic artery, or anomalous low insertion of the right superior caval vein. 156,182,205,206 In at least one patient with a falsepositive scimitar sign, azygos continuation of the inferior caval vein was noted, and was likely responsible for the abnormal silhouette.…”
Section: Scimitar Syndromementioning
confidence: 99%
See 2 more Smart Citations